Peran Kepala Sekolah sebagai Manajer dalam Penerapan Kurikulum Merdeka di Madrasah Ibtidaiyah Darussalam Jelutung Kota Jambi - Umi Latifah; Mahluddin Mahluddin (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the role of the principal as a manager in implementation of the Independent Curriculum at Madrasah Ibtidaiyah Darussalam Jelutung, Jambi City. The method used is qualitative research with a case study approach. Data was collected through interviews, observation and documentation. The research results show that: 1) The school principal has a significant role starting from planning, organizing, implementing and evaluating the curriculum. 2) There are obstacles for the principal in carrying out his role as a manager in implementing the Independent Curriculum, namely that it takes a long time and is not easy for the principal to study the Independent Curriculum, time constraints and the physical condition of the principal as well as teacher motivation and understanding that need to be improved. 3) The school principal takes proactive steps to resolve these obstacles, such as increasing the principal's personal understanding, carry out rescheduling and time management, as well facilitating teachers in increasing their understanding and professionalism through training, participating in routine KKG activities, and direct coaching.